Attitudes of U.P. female educators ages 50 and above towards shopping for clothes - Trinidad, Gugma Maria L.
With a unique cultural background, Filipino consumers (specifically older women) present a totally different attitude towards shopping for clothes from those of Western consumers. This study was conducted for the purpose of determining the attitudes of U.P. female educators ages 50 and above towards shopping for clothes. The descriptive method of research was utilized and the normative survey technique was used for gathering data. The questionnaire served as the instrument for collecting data. Convenience sampling was used to gather the sample of 49. Only those aged 50 years and above, and full time educators in U.P. Diliman were considered as qualified respondents. Majority of the sample were married female educators with a graduate/professional degree, mostly between the ages of 55-59. Most of the respondents had a total household income above P300,000 and a clothing expenditure of P6,000-P12,000 last year (refers to year 2001). Findings revealed that the majority of the respondents do not follow any specific routine when shopping. In addition, although the respondents preferred to shop only when there is a need, they often end up making unplanned purchases. Most of the respondents were willing to spend P301-P500 for a blouse, for a skirt, or for a pair of pants/slacks. The vote was split between P701-P1,000 and more than P1,000 when asked about how much they were willing to pay for a dress. A number of the respondents indicated willingness to spend P701-P1,000 on a coat/jacket. The most common method of payment among the respondents was cash, and when asked about sales (year-end sales, Christmas sales, etc.), majority of the respondents reported taking advantage of such. Most of the respondents preferred to shop on weekends, or any day of the week, alone, or with the family members. The survey revealed that the most patronized type of retail organization is the better quality department store. The most influential store characteristics to the respondents' shopping decisions were location and convenience, merchandise assortment, promotional deals and point-of-purchase displays. Friends, relatives, store ads, and magazines were the most influential interpersonal and mass media references by the respondents. Fit and comfort was reported as the most important clothing variable by the respondents, followed by style, fabric quality, and price. The respondents indicated the highest satisfaction with the price variable. Through factor analysis, four groupings were extracted from the importance placed on the ten clothing variables specified by the study. Care, fabric quality, wardrobe coordination, durability, occasion appropriateness, and print comprise the first grouping (practical shoppers); color and style compose the second (aesthetic shoppers); fit and comfort and price respectively comprise the third (comfort shoppers) and the fourth components (economic shoppers).